The Influence Of Emotional Intelligence, Work Ethic And Motivation On The Performance Of Health Control Service Employees Population And Family Planning Sidenreng Rappang District - Said, Muh; Rahman, Basri (YUME : Journal of Management, 2024)
The results of the research show that 1) The emotional intelligence variable has no effect on the performance of employees of the Population Control and Family Planning Health Service of Sidenreng Rappang Regency with a value of t-count> t-table (1.427 < 2.002) work ethic has a positive and significant effect on the performance of employees of the Health Control Service Population and Family Planning of Sidenreng Rappang Regency with t-count > t-table (4,173 > 2002) on the third variable, namely 3) motivation has a positive and significant effect on the performance of employees of the Population Control and Family Planning Health Service of Sidenreng Rappang Regency. because t-count >.table (6,002 <2,002), 4) In the simultaneous test, the variables emotional intelligence, work ethic and motivation simultaneously had a positive and significant effect on the performance of the Sidenreng Rappang District Population Control and Family Planning Health Service. because F-count > F-table (36,094 > 2.77), while the determination test contributed 65.9% to employee performance, while the rest was influenced by other variables not included in the research. Keywords: Emotional intelligence, work ethic, motivation, employee performance.